Are surgical outcomes for one level anterior decompression and fusion associated with MRI parameters for degenerative cervical myelopathy? - Luqiang Qu; Luqiang Qu; Shaofeng Yang; Lijie Yuan; Junjie Niu; Dawei Song; Songping Yang; Huilin Yang; Jun Zou (Frontiers in Surgery, 2022)
BackgroundOur study is to determine the correlation between preoperative MRI parameters of spinal cord compression and the effects of anterior surgery in patients with degenerative cervical myelopathy (DCM).Methods24 normal subjects with no evident abnormalities were selected as group A. 79 patients with DCM underwent single-segment (C4–5/C5–6) ACDF surgery formed the operation group, and separated into group B (without high signal) and group C (with high signal) according to the absence or presence of high signal in the spinal cord on preoperative T2-weighted MRI respectively. MRI parameters (MCC, maximum canal compromise; MSCC, maximum spinal cord compression; CR, spinal cord compression rate; RCSCDS, ratio of cervical spinal cord to dura sac) were measured. The JOA score was used to evaluate cervical spinal cord function and recovery rate (RR) was used to evaluate postoperative efficacy. The relationship between preoperative MRI parameters and postoperative efficacy was analyzed.ResultsThe preoperative JOA score and RR of group B were higher than that of group C. MCC and MSCC in group B were significantly lower than those in groups C. The multiple linear regression equation was the fitted postoperative JOA score = 13.371–2.940 * MCC −5.660 * RCSCDS +0.471 * preoperative JOA score. The fitted RR = 1.451–0.472 * MCC −1.313 * RCSCDS.ConclusionThe occurrence of high signal on T2-weighted images could reflect more serious spinal cord injury. The postoperative JOA score was significantly correlated with MCC, RCSCDS, and preoperative JOA score, while RR was significantly associated with MCC and RCSCDS.